THE EFFECTIVENESS OF USING ENGLISH SONGS TOWARDS STUDENTS’ VOCABULARY MASTERY AT THE ELEVENTH GRADE OF SMAN 1 TEMBILAHAN HULU - Agus Mustajib; Hanissa; Edi Ardian (Program Studi Pendidikan Bahasa Inggris, 2025)
This quasi-experimental study examines the effectiveness of using English songs to enhance vocabulary mastery among eleventh-grade students at SMAN 1 Tembilahan Hulu. The research design involved two groups: the experimental group (class XI MIPA 2) and the control group (class XI MIPA 3), with 32 and 34 students respectively, totaling 66 students. The primary objective of the study was to identify significant differences in English vocabulary mastery between students taught using song media and those taught using conventional methods. Additionally, the study aimed to evaluate the overall effectiveness of using songs as a teaching medium for vocabulary enhancement. Data collection involved administering pre-tests and post-tests to both groups to measure vocabulary mastery before and after the treatment. The experimental group received instruction through English songs, while the control group continued with conventional teaching methods. The data were analyzed using SPSS 27 for Windows, focusing on hypothesis testing and discussions to draw meaningful conclusions. The results revealed a significant improvement in the vocabulary mastery of students in the experimental group compared to those in the control group. The average pre-test score for the experimental group was 22.50, which increased to 45.77 in the post- test, while the control group’s average score increased from 21.34 in the pre-test to 32.98 in the post-test. The statistical analysis showed a significance level of Asymp. Sig. (2-tailed) 0.001, which is less than the threshold of 0.050, indicating a statistically significant difference. These findings suggest that the use of English songs as a teaching medium is more effective than conventional methods in enhancing vocabulary mastery among eleventh-grade students at SMAN 1. Tembilahan Hulu. The study highlights the potential benefits of incorporating music into language instruction to create a more engaging and effective learning experience for students.